2011
DOI: 10.1093/infdis/jiq051
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal Infections of Mice by Low Numbers of African Trypanosomes Are Controlled by Innate Resistance but Enhance Susceptibility to Reinfection

Abstract: Antibodies are required to control blood-stage forms of African trypanosomes in humans and animals. Here, we report that intradermal infections by low numbers of African trypanosomes are controlled by innate resistance but prime the adaptive immune response to increase susceptibility to a subsequent challenge. Mice were found 100 times more resistant to intradermal infections by Trypanosoma congolense or Trypanosoma brucei than to intraperitoneal infections. B cell–deficient and RAG2−/− mice are as resistant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(74 citation statements)
references
References 43 publications
6
65
2
1
Order By: Relevance
“…Neither parasitological nor serological tests are sensitive and specific enough to differentiate between them, thus various kinds of genetic and molecular methods have been continually updated in order to enhance greater precision in the diagnosis of Trypanozoon species and differentiation of these pathogens [4]. In addition, characterization and comparative analysis of genomes of such closely-related T. evansi allow their identification at the strain and may generate a testable hypothesis of genes that might be responsible for differences in pathologies between parasite strains or subspecies [5]. A series of techniques based on PCR have been used for phylogenetic analysis and/or characterization of polymorphisms in T. evansi populations around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Neither parasitological nor serological tests are sensitive and specific enough to differentiate between them, thus various kinds of genetic and molecular methods have been continually updated in order to enhance greater precision in the diagnosis of Trypanozoon species and differentiation of these pathogens [4]. In addition, characterization and comparative analysis of genomes of such closely-related T. evansi allow their identification at the strain and may generate a testable hypothesis of genes that might be responsible for differences in pathologies between parasite strains or subspecies [5]. A series of techniques based on PCR have been used for phylogenetic analysis and/or characterization of polymorphisms in T. evansi populations around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Cells were cultured at a concentration of 5 ϫ 10 6 /ml (200 l/well) in 96-well tissue culture plates with or without lysates of T. brucei VAT 10-26 parasites in a humidified incubator containing 5% CO 2 . The parasite lysates were made by repeated freezing and thawing, and sonication, as described previously (35). The culture supernatant fluids were collected after 48 h, centrifuged at 1,500 ϫ g for 10 min, and stored for cytokine assays at Ϫ20°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…S1). To confirm the antigen specificity of IFN-␥ production by CD4 ϩ T cells, we measured the secretion of IFN-␥ by spleen cells from naïve mice and infected mice in the absence or presence of various concentrations of T. brucei VAT 10-26 lysate antigens as described previously (35). Although there was no significant difference in IFN-␥ secretion between the absence and the presence of the parasite lysates for infected mice, spleen cells purified from infected wild-type mice or infected mice depleted of CD8 ϩ T cells, but not from infected mice depleted of CD4 ϩ T cells, secreted significantly larger amounts (P Ͻ 0.01) of IFN-␥ than spleen cells from naïve mice (undetectable) when cultured with trypanosome lysates (see Table S1 in the supplemental material).…”
Section: Mortality Mediated By Cd8 ؉ T Cells Is Not Associated With Imentioning
confidence: 99%
“…Although BALB/c mice are highly susceptible to intraperitoneal infection with Trypanosoma congolense (14), a recent report showed that these mice are relatively resistant to an intradermal infection route (18). Paradoxically, primary intradermal low-dose infection predisposes to enhanced susceptibility following rechallenge infection (18).…”
Section: Primary Low-dose Id T Congolense Infection and Susceptibimentioning
confidence: 99%
“…infection model shows that the outcome of i.d. infection is very different, with mice being relatively (about 1,000 times) more resistant to the intradermal than the intraperitoneal route (18). Paradoxically, primary low-dose intradermal infection predisposes to enhanced susceptibility following a challenge infec-tion.…”
mentioning
confidence: 99%